Design of a wireless motor drive system for robotic applications - Sajikumar, Adwaith (Nanyang Technological University, 2025)
This dissertation presents the design, simulation, and evaluation of a low-power wireless motor drive system for robotic applications. Traditional motor drives rely on wired connections for power transmission, which impose limitations such as restricted mobility, mechanical wear, and safety risks. This research integrates Wireless Power Transfer (WPT) with Permanent Magnet Synchronous Machines (PMSMs) to develop a wireless motor drive system that eliminates these constraints. The proposed system is analyzed through MATLAB/Simulink simulations, where various WPT compensation topologies are evaluated. Phase Shift Modulation (PSM) is implemented to regulate the DC-link voltage, ensuring stable operation under varying load conditions. The results indicate that the SS and LCC-LCC topologies offer improved voltage stability and operational performance. Key findings show that the SS-compensated system supports loads up to 0.3 Nm at 220 rpm, while the SP topology exhibits limitations be yond 0.2 Nm at 260 rpm. The LCC-LCC topology demonstrates superior volt age regulation. This study successfully demonstrates the feasibility of a wireless PMSM motor drive and highlights potential areas for improvement. Future research could focus on dynamic DC-link voltage control, hybrid capacitive inductive WPT, adaptive compensation techniques, and experimental prototyping to further enhance system efficiency and power transfer capabilities.